ALGORITHM AND COMPUTER PROGRAM FOR DETERMINATION OF HIGH PRECISION VALUE OF PHYSICAL QUANTITY AND PARAMETERS OF UNSTABLE TRANSFORMATION FUNCTION - КОРОГОД, Г. О.; ВОЛІВАЧ, А. П. (Technologies and Engineering, 2023)
The purpose of the work is the development of an algorithm and a computer program aimed at obtaining a high-precision value of a physical quantity with an unstable transformation function of the sensor, determining the current values of the parameters of the transformation function and establishing their compliance with tolerance limits. Methodology: theory and methods of redundant measurements of physical quantities for the correct use of the methodology of redundant measurements, theory of errors for determining and estimating errors, theory of algorithms for the structured construction of algorithms, analytical methods of analysis of signal transformation processes, methods of mathematical modeling and numerical methods for solving nonlinear equations quantities and systems of equations of quantities, methods of computer analysis for the logical construction of software components. Results: the proposed algorithm and the computer program built on its basis for processing the obtained measurement results allow: 1) to determine the high-precision value of the desired physical quantity, which does not depend on changes in the parameters of the transformation function, based on the equations of redundant measurements; 2) determine the current values of the parameters of the unstable transformation function; 3) to set qualitative indicators of deviations of each of the parameters of the sensor transformation function. Scientific novelty: the developed algorithm for the operation of redundant measurements with a linear and unstable transformation function and its computer implementation create opportunities for conducting a calculation experiment and further research of its results. Practical significance: the implementation of the algorithm and computer program using the method of redundant measurements allows to determine the high-precision value of the desired physical quantity and directly carry out effective studies of redundant measurements with an unstable transformation function of the sensor. In addition, due to the determination of the current values of the parameters of the transformation function, it becomes possible to determine the metrological reliability of the sensor with given deviations.